Perfil de ácidos grasos en diferentes materiales de Chenopodium quinoa - Bordoni, Antonella; Veggetti, Mariela Iris; Rossetti, Luciana; Rizzo, Sergio Anibal; Cunzolo, Sebastián Abel; Descalzo, Adriana Maria (Universidad Nacional de Quilmes, 2024)
Poster